Financing micro-businesses and UNCITRAL's model law on secured transactions - Gullifer, L; Tirado, I (University of Oxford Faculty of Law, 2017)
An overwhelming proportion of businesses in the world are very small, consisting of just one person with no or very few employees. Despite the small size of such businesses, it is extremely important to the economic wellbeing of states that they thrive and grow. In order to achieve this, access to finance is critical. While there have been some positive developments towards this goal, such as Government-run programmes to foster the creation of start-ups (mostly micro-businesses) and to enhance access to finance for smaller enterprises, or the widespread growth of microfinance in developing and middle income countries,1 these measures tend to be limited in their operation and usefulness. Secured financing, especially when provided by financial institutions, is necessary for most micro-businesses to achieve their potential, but access to this type of financing is, at present, restricted and, in some situations, non-existent. The legal structure for secured financing provided by the UNCITRAL Model Law can alleviate some of the problems preventing access to secured financing for micro-businesses. This paper examines these problems, and the difference that adoption of the Model Law system could make. It also identifies some areas in which the Model Law is not entirely suitable for the financing of micro-businesses, as well as specific issues which must be addressed by other areas of law and regulation if financing to micro-businesses is to flourish. While the primary focus is on micro-businesses in developing economies, it is suggested that the problems faced by micro-businesses in accessing finance arise even in the more developed jurisdictions, and that at least some of the solutions suggested are appropriate for consideration in all parts of the world.